Copper (II) complexes with Ac-HXH-NHMe (X=Gly, Ala and Aib) peptide motifs: Influence of increasing CH3 groups at Cα of residue X on the coordination in solution - Singh R.K.; Srivastava V.C.; Singh U.P. (My University, 2025)
The interaction of Cu(II) ion with small peptides has been an interesting subject to clarify the role of copper in detail. As various Cu(II)-oligopeptide complexes can also be good models for the active centers of metalloenzymes, complexes of tripeptide and tetrapeptides are frequently investigated instead of the complexes of large peptides. The histidine side-chains of various metalloproteins frequently take part in the copper(II) coordination. Accordingly, we studied the coordination of Cu(II) to the N and C terminal protected tripeptide ligands LA (Ac-HisGlyHis-NHMe), LB (Ac-HisAlaHis-NHMe) and LC (Ac-HisAibHis-NHMe) in aqueous solution potentiometrially in order to determine the effect of Cα methyl groups at middle residue acid on the ligation of the backbone NH and also on histidine's Nim of coordination. Species distribution curves indicates that in acidic pH, all three peptides behave as bidentate ligands and a macrochelate forms on the metal coordination with the two histidine imidazolyl N. This coordination remains unaffected with the +I effect of increasing CH3 groups at Cα of middle residue. In the pH range 4-8, the tridentate coordination from the peptide is seen in ligand L A and LB while it is absent in LC due to +I effect of two Cα methyl groups at middle residue as they makes N-terminal NH deprotonation difficult in this pH range and it takes place along with C terminal NH and only 4N coordinated species formed at higher pH. These 4N (Nim, N-, N-, Nim) coordinated species are formed by all the three ligands at higher pH values. © 2007 Bentham Science Publishers Ltd.